THE POTENTIAL OF HALAL FOOD ON THE ECONOMY OF THE COMMUNITY IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Hisam, Ahyani; Mahfud, Muntaha; Rohmat, Waluyo; Widadatul, Ulya; Muharir, M (Pusat Kajian Halal Undip, 2020)
Abstract: Introduction / Main Objective: This study aims to determine the potential of halal food to the economy of the community in Wangon sub-district, Banyumas district, Central Java province and Lakbok district, Ciamis district, West Java province, and Kedungreja district, Cilacap district, Central Java province. Background: In the halal food sector or halal food in Indonesia, especially in the Industrial Revolution Era 4.0 as it is now, it has become a demand. This is because Indonesia is one of the largest Muslim population in the world. No exception in these three districts (Banyumas and Ciamis and Cilacap). Research Methods: This study uses field methods and collects data obtained by means of observation and interviews and documentation. Novelty: related to the research on the potential of halal food on the economy of the people in Ciamis Regency, Central Java Province and Banyumas Regency, Central Java Province and Kedungreja District, Cilacap Regency, so far no one has researched it. Findings: Halal Food in three districts, namely Ciamis Regency and Banyumas Regency and Ciamis Regency is able to boost the economy in the region, as evidenced by the Welfare of the local community to fulfill their daily needs. Conclusion: Halal Food in three districts, namely Ciamis Regency and Banyumas Regency and Cilaca Regency is able to boost the economy in the region including a variety of foods that have been labeled halal or not labeled halal. Among them from cassava ingredients (Ciu, Tape, Kripik, Cimplung / Kulub), from soybean ingredients (Tempe Mendoan, and Sule), from coconut juice / (legen in Javanese) can be used (Brown Sugar / Javanese Sugar and Apem Mixes) .Â Keywords: Halal Food, Tourism, EconomyÂ Abstrak: Pendahuluan/Tujuan Utama : Penelitian ini bertujuan untuk mengetahui potensi halal food terhadap perekonomian masyarakat di kecamatan Wangon, Kabupaten Banyumas, Provinsi Jawa Tengah dan Kecamatan Lakbok Kabupaten Ciamis, Provinsi Jawa Barat, serta Kecamatan Kedungreja Kabupaten Cilacap Provinsi Jawa Tengah. Latar belakang : di Sektor pangan halal atau halal food di Indonesia khususnya di Era Revolusi Industri 4.0 seperti sekarang ini telah menjadi tuntutan. Hal ini dikarenakan Indonesia masuk pada penduduk muslim terbesar di Dunia. Tidak terkecuali di tiga Kabupaten tersebut juga demikian (Banyumas dan Ciamis serta Cilacap). Metode Penelitian : Penelitian ini menggunakan Metode lapangan dan mengumpulkan data yang diperoleh dengan cara observasi dan wawancara serta dokumentasi. Kebaruan Penelitian : terkait penelitian potensi halal food terhadap perekonomian masyarakat di Kabupaten Ciamis Provinsi Jawa Tengah dan Kabupaten Banyumas, Provinsi Jawa Tengah serta Kecamatan Kedungreja Kabupaten Cilacap sejauh ini belum ada yang meneliti. Hasil Temuan : Halal Food di tiga Kabupaten yakni Kabupaten Ciamis dan Kabupaten Banyumas serta Kabupaten Ciamis mampu mendogkrak perekonomian di wilayah tersebut, dibuktikan dengan Kesejahteraan para Masyarakat setempat guna mencukupi kebutuhan sehari-hari. Kesimpulan : Halal Food di tiga Kabupaten yakni Kabupaten Ciamis dan Kabupaten Banyumas serta Kabupaten Cilacap mampu mendogkrak perekonomian di wilayah tersebut meliputi aneka makanan yang sudah berlabel halal maupun belum berlabel halal. Diantaranya dari bahan singkong (Ciu, Tape, Kripik, Cimplung/Kulub), dari bahan kedelai (Tempe Mendoan, dan Sule), dari bahan Nira Kelapa/ (legen dalam bahasa Jawa) dapat dijadikan (Gula Merah/Gula Jawa dan Campuran Apem).Â Kata Kunci: Halal Food, Pariwisata, Ekonomi